The relationship between perceived social support and rumination among parents of children with autism: moderating effect of the degree of intervention received by children - Xu, Li; Song, Li; Xiong, Zhiheng; Chen, Jiejia (Frontiers in Psychiatry, 2024)
Objective: As the number of children diagnosed with autism rises year by year, the issue of nurturing this particular group becomes increasingly salient. Parents of autistic children, as the nearest and most reliable caregivers for their children, shoulder immense psychological strain and accountability. They are compelled to confront an array of daily life challenges presented by their children, as well as endure multiple pressures such as societal scrutiny and financial burdens. Consequently, the mental health status of the parents is of utmost significance.In this study, questionnaire survey combined with literature analysis were applied. The rumination thinking scale and the social support scale were used to investigate the relationship between social support perceived by parents of autistic children and rumination. Meanwhile, the moderating effects of intervention on children with autism were also explored. It hopes that our research would provide a basis for alleviating psychological stress and improving the mental health levels of the parents. A total of 303 parents of children with autism were collected (including 160 females and 143 males). Corresponding data analyses were conducted using SPSS 26.0.Results: Parents of autistic children generally exhibited high levels of rumination, with significant gender differences. At the same time, the perceived social support by the parents significantly influenced their level of rumination. It showed that the higher the social support received by parents, the lower the level of rumination. More importantly, the extent of intervention received by the children had a regulating effect on rumination of their parents.The personalized psychological support programs should be developed based on the actual situation of parents, to better manage the challenges presented by raising a child with autism.Our findings would provide important theoretical underpinnings and practical guidance for psychological intervention efforts aimed at families of autistic children. Moreover, these findings offer novel insights for future research, with the potential to advance the field of mental health studies concerning parents of children with autism.